Acetic Acid Supplementation: Effect on Resting and Exercise Energy Expenditure and Substrate Utilization - COBB, KOLTON M. (Int J Exerc Sci, 2021)
The purpose of this study was to investigate the influence of acetic acid (apple cider vinegar; ACV) supplementation on resting and exercise energy expenditure and substrate utilization. Using a randomized, double blind, crossover design, 16 healthy subjects were supplemented for 4 d with either ACV (30-ml/d) mixed in 1 L of a non-nutritive lemon-flavored drink or a placebo (PLA). They were then assessed via indirect calorimetry for resting energy expenditure (REE) and substrate utilization. This was immediately followed by the assessment of steady state cycling exercise energy expenditure at 40 W (EEE-40) and 80 W (EEE-80) and substrate utilization. Results: Neither REE nor resting substrate utilization were significantly different between groups (p ≥ .05). During cycling exercise at both 40W and 80W, there were no significant differences observed between groups for energy expenditure (EEE-40: ACV 4.13 ± 0.79, PLA 4.37 ± 0.61 kcal/min; EEE-80: ACV 6.09 ± 0.87, PLA 6.26 ± 0.72 kcal/min) or substrate utilization (40W carbohydrate: ACV 0.72 ± 0.19, PLA 0.76 ± 0.16; fat: ACV 0.15 ± 0.07, PLA 0.16 ± 0.06 g/min), (80W carbohydrate: ACV 1.28 ± 0.32, PLA 1.34 ± 0.35; fat: ACV 0.14 ± 0.10, PLA 0.14 ± 0.10 g/min) (p ≥ .05). Conclusions: Recent findings suggest that chronic acetic acid supplementation is associated with significant reductions in body weight and body fat; however, the findings of the present study suggest that a semi-acute (4 d) acetic acid supplementation does not impact resting or exercise energy expenditure or substrate utilization.